Adsorption of Methylene Blue Dye onto Various Marine Sediments and Seagrass Biomass of Posidonia oceanica Species: Kinetics and Equilibrium Studies - Maria C. Vagi; Andreas S. Petsas; Dionysia Dimitropoulou; Melpomeni Leventelli; Anastasia D. Nikolaou (Organics)
This study concerns the investigation of the sorption and desorption phenomena of the organic dye methylene blue (MB) on three different marine sediments and non-living biomass of the seagrass species Posidonia oceanica. All tested adsorbents were of natural origin and were collected from unpolluted coasts of the North Aegean Sea (Greece). The batch equilibrium technique was applied and MB concentrations were determined by spectrophotochemical analysis (λ = 665 nm). The experimental results showed that all four isotherm models, Freundlich, Langmuir, Henry, and Temkin, could describe the process. The normalized to organic matter content adsorption coefficients (KOM) ranged between 33.0765 and 34.5279 for the studied sediments. The maximum adsorption capacity (qmax) of sediments was in the range of 0.98 mg g−1 and 6.80 mg g−1, indicating a positive correlation with the adsorbents’ organic matter content, textural analysis of fine fraction (<63 μm), and specific surface area. The bioadsorption of MB on P. oceanica biomass resulted in 13.25 mg g−1 up to 17.86 mg g−1 adsorption efficiency. Desorption studies revealed that the studied dye in most cases was very strongly adsorbed on studied matrices with extremely low quantities of seawater extractable amounts (≤1.62%). According to the experimental findings, phycoremediation by using P. oceanica can be characterized as an efficient method for the bioremediation of dye-polluted wastewater.